2015
DOI: 10.1007/s10661-015-4609-0
|View full text |Cite
|
Sign up to set email alerts
|

Response of micro- and mesozooplankton in the southwestern Bay of Bengal to a cyclonic eddy during the winter monsoon, 2005

Abstract: A cyclonic eddy (CE) in the southwestern Bay of Bengal (SWBoB; 10-15° N; 81-87° E) during winter monsoon 2005 and associated changes in the open ocean hydrography and productivity patterns were studied using satellite observations and in situ measurements. Analysis of the satellite-derived sea surface height anomaly (SSHA) indicated the existence of a large eddy (10-15° N; 81-87° E) from November to January, with its core centered at 13° N and 82° E. The large positive wind stress curl (~1.8 × 10(-7) N m(-2)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
1
1
1
Order By: Relevance
“…The results about species assemblages of zooplankton agree with literature descriptions about Arabian Sea, due high productivity, although there are marked seasonal density fluctuations due monsoons (Vineetha et al 2015;Vishnu Radhanan et al 2015;Gupta et al 2016). Within the zooplankton species, Copepods by their sheer and diversity constitute the most important group in any zooplankton community (Anbazhagan, 1988;Jayalakshmi et al 2015;Vineetha et al 2015), because they occupy an important position in the trophic structure and play a major role in the energy transfer of any aquatic environment. Because of their predominance, copepods form the chief index of utilization of biotope at secondary level (Madhupratap & Haridas, 1975;Madhupratap, 1979;Gupta et al, 2016).…”
Section: Resultssupporting
confidence: 84%
“…The results about species assemblages of zooplankton agree with literature descriptions about Arabian Sea, due high productivity, although there are marked seasonal density fluctuations due monsoons (Vineetha et al 2015;Vishnu Radhanan et al 2015;Gupta et al 2016). Within the zooplankton species, Copepods by their sheer and diversity constitute the most important group in any zooplankton community (Anbazhagan, 1988;Jayalakshmi et al 2015;Vineetha et al 2015), because they occupy an important position in the trophic structure and play a major role in the energy transfer of any aquatic environment. Because of their predominance, copepods form the chief index of utilization of biotope at secondary level (Madhupratap & Haridas, 1975;Madhupratap, 1979;Gupta et al, 2016).…”
Section: Resultssupporting
confidence: 84%
“…One exception was a slight decrease in DO concentration (~5 mmol kg -1 ) in the cyclonic eddy around 12 -13 September 2020 (Figures 6E, F). This decrease is in contrast with previous studies reporting that DO concentrations in the cyclonic eddies were higher than in the outer areas of the cyclonic eddies (Sukigara et al, 2014;Jayalakshmi et al, 2015). The studies ascribed the increase in DO concentration to upward nutrient supply resulting in enhanced biological production.…”
Section: Effects Of Eddies On Biogeochemistrycontrasting
confidence: 95%
“…From the ship‐based in situ observations, Naik et al () have reported an enhancement of 5 μM in the nitrate concentration in the near‐surface layer after the passage of a TC in the Arabian Sea. Similarly, Jayalakshmi et al () have also reported the increase of 3.8 μM in nitrate concentration at a cyclonic eddy region in the southwestern BoB during northern winter.…”
Section: Resultsmentioning
confidence: 66%